Kajian Eksperimental Daya dan Konsumsi Bahan Bakar Mesin Pembakaran Internal dengan Bioetanol dari Sorgum sebagai Sumber Energi Terbarukan - Sugiyarto, Sugiyarto; Muhammad, Rouf (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
The dependence on fossil fuels as a primary energy source has led to serious environmental and economic problems, including the scarcity of non-renewable natural resources and significant environmental impacts. There is a need to find cleaner and more sustainable renewable energy sources to reduce dependence on fossil fuels and mitigate environmental damage. One promising alternative is bioethanol from sorghum (Sorghum Bicolor). The liquid from sorghum stalks is fermented and distilled to produce bioethanol, which is then blended with gasoline (Pertamax) in various concentrations (E10, E20, and E30). A dynotest was used to measure the power output, and a measuring cup was used to test the fuel consumption of a single-cylinder gasoline engine at idle speed. Engine power and fuel consumption were the parameters analyzed. The research showed that the higher the bioethanol content in the fuel, the more fuel-efficient it became, but the higher the power output generated by the engine. The E30 blend produced the best results in terms of engine power and fuel consumption. This is due to the more uniform fuel mixture, which results in better fuel expansion. These findings support sorghum bioethanol as a sustainable alternative fuel and promote a shift towards clean energy in industry and transportation.